Solvothermal synthesis of CdS nanowires templated by polyethylene glycol - Thongtem T. (2014)
CdS nanowires were solvothermally synthesized from Cd(NO3)2 and S powder using ethylenediamine as a solvent and polyethylene glycol (PEG) as a template. Hexagonal CdS with P63mc space group was detected using XRD and SAED, results which are in good accordance with those obtained by the simulation. SEM, TEM and HRTEM revealed the gradual development of nanowires in the [0 0 1] direction with a number of atoms aligning in a crystal lattice. Raman spectra of different products showed the fundamental and overtone modes at the same wavenumbers of 300 and 601 cm-1, respectively. Their relative intensities at different molecular weight PEG were influenced by the anisotropic geometry of the products. Their photoluminescence peaks were detected at the same wavelengths of 518 nm. A formation mechanism for CdS nanowires was also proposed to relate to the experimental results. © 2009 Elsevier Ltd and Techna Group S.r.l.